Piscicidal Efficacy of Selected Plant Products against Murrel (Channa spp) in Tripura, Northeast India: A Bioassay Study: Plant-based Piscicides: Evaluating Toxicity on Murrel Fish - Debnath, Chandan; Lopamudra Sahoo (Fishery Technology, 2024)
The objective of the study was to investigate the piscicidal efficacy of Camellia sinensis (Tea) leaves, Jatropha curcas (Bherenda) seeds, Hevea brasiliensis (Rubber) seeds, Tephrosia purpurea (Bannilgach) leaves and Trichosanthes tricuspidata (Makal) fruits against Murrel (Channa spp). Aqueous extracts were these prepared (in a ratio of 1:5) using locally sourced materials from Tripura. These extracts were then subjected to a static bioassay technique, which was performed for 24 and 48 hours in glass aquaria. Test concentrations ranged from 5-100 ml/L. The behavioral responses of the fish were recorded upon exposure to the extracts, and the absence of reflexes was regarded as an indication of fish mortality. The median lethal concentrations (LC50) of the extracts were determined by plotting fish mortality against the test concentrations. Among the tested substances, tea leaves exhibited the highest effectiveness, followed by Tephrosia leaves, Jatropha seeds, Trichosanthes fruits, and Rubber seeds. The 24 hour LC50 values varied from 11.0 to 52.5ml/L, while the 48 hour LC50 values ranged from 9.4 to 29.5 ml/L. The results of this study suggest that tea leaves, bherenda and rubber seeds, bannilgach leaves, and makal fruits have the capacity to function as viable piscicides.